2011
DOI: 10.4081/reumatismo.2010.91
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid in Rheumatology: mechanisms of action and severe adverse events

Abstract: MPA is clinically administered as morfolinoethyl ester (mycophenolate mofetil, MMF) or, more recently, as a salt (enteric-coated mycophenolate sodium). It is a fermentation product of Penicillium brevicompactum and other analogue fungi, identified by Gosio in 1893 as a weak antibacterial agent; in 1969 Franklin and Cook discovered its capacity to inhibit the inosine mono phosphate dehydrogenase (IMPDH), an enzyme involved in purine nucleotide synthesis (1)..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…However, detection of PAH usually occurs so late that reduction of disease activity alone is not sufficient to control PAH. A case of resolution of PAH and interstitial lung disease in an SLE patient after treatment with mycophenolate mofetil was described [57]. This is consistent with animal model studies in which the active metabolite of mycophenolate mofetil has been shown to inhibit pulmonary artery wall remodeling in rats.…”
Section: Does Diagnosis Of Pulmonary Arterial Hypertension Change the Management Of A Patient With Connective Tissue Disease?supporting
confidence: 74%
“…However, detection of PAH usually occurs so late that reduction of disease activity alone is not sufficient to control PAH. A case of resolution of PAH and interstitial lung disease in an SLE patient after treatment with mycophenolate mofetil was described [57]. This is consistent with animal model studies in which the active metabolite of mycophenolate mofetil has been shown to inhibit pulmonary artery wall remodeling in rats.…”
Section: Does Diagnosis Of Pulmonary Arterial Hypertension Change the Management Of A Patient With Connective Tissue Disease?supporting
confidence: 74%
“…In the following years, a multitude of effects on different cell types, e.g. lymphocytes, monocytes, neutrophils as well as on dendritic, mesangial, mast, vascular smooth muscle and endothelial cells were discovered . The authors concluded in their literature review that while rheumatic patients still largely benefited from MPA treatment, it holds the risk of immune suppression, and therapy has been associated with several, sometimes life-threatening, infections by viruses.…”
Section: Formation Toxicity and Occurrence Of Emerging Mycotoxinsmentioning
confidence: 99%
“…Inhibition of inosine monophosphate dehydrogenase (IMPDH), the rate-limiting enzyme in de novo synthesis of guanosine nucleotides 34 Antiproliferative effects on T and B lymphocytes, monocytes, fibroblasts, endothelial, mesangial and vascular smooth cells Induction of apoptosis in lymphocytes, monocytes Induction of necrosis in lymphocytes Reduction of cytokine production by T lymphocytes, dendritic cells and endothelial cells Reduction of immunoglobulin production by B lymphocytes Reduction of chemotaxis to inflammation sites in monocytes and lymphocytes Inhibition of cell-cell interaction and endothelial adhesion in monocytes, dendritic cells, neutrophils and fibroblasts Other: inhibition of mast cell degranulation, of nitric oxide production by endothelial cells; suppression of fibroblast ability to migrate, adhere and heal wounds; inhibition of extracellular matrix production in human mesangial cells 33 Prodrug of mycophenolic acid (MPA), which acts as an inhibitor of inosine monophosphate dehydrogenase (IMPDH) Azathioprine (AZA) Mercaptopurine metabolites are incorporated into replicating DNA, halting replication, as well as blocking the pathway for purine synthesis. Cytostatic and immunosuppressive action 35 Interference with T and B cell proliferation Synthetic purine analog derived from 6-mercaptopurine Methotrexate (MTX)…”
Section: Glucocorticoidsmentioning
confidence: 99%